3D printing eco-friendly concrete containing under-utilised and waste solids as aggregates. (July 2021) - Bai, Gang; Wang, Li; Ma, Guowei; Sanjayan, Jay; Bai, Mingke
Abstract: 3D concrete printing is an emerging construction technology, and presents an opportunity for utilising materials that are otherwise considered unsuitable for concrete construction. Incorporating underutilised solids and/or waste solids as aggregates is a way of gaining the maximum environmental and economic benefits from the emerging 3D concrete printing technology. In this study, desert sand (small size), river-sediment ceramsite sand (medium size), and recycled concrete (large size) were experimentally investigated for use as aggregates in the 3D printing of concrete. Three mixtures were designed with continuous, open, and interrupted gradations of solids, respectively, based on the theory of particle interference, and aiming to meet the requirements of extrusion-based 3D printing. The influences of the particle grading characteristics on the printability-related early-age behaviours, mechanical properties, and shrinkage resistance have been measured and analysed. The test results demonstrate that the self-supporting skeletal effect formed by the gradated particles reduces the flowability of the mixtures, but the structural build-up/buildability performance is improved (under the premise of the desired printability). The interlayer distribution and skeleton of the gradated aggregate contribute to improving the interfacial interlocking effect and contact bonding between layers; this is visually validated through computed tomography (CT) scanning. Further, the addition of aggregates reduces the proportion of cementitious composites, and therefore effectively mitigates the shrinkage of the cement matrix. The grading characteristics of the underutilised particle resources are crucial for regulating the early-age 3D printability. This article provides feasible solutions based on experimental data for promoting the eco-utilisation of underutilised and waste solids in 3D printing, and these solutions satisfy the minimum strength and durability requirements. Highlights: Desert sand, ceramsite particles, and recycled aggregate were adopted for the manufacturing of 3D printed materials. The influences of three types of particle gradings on the printability and mechanical properties were investigated. The instantaneous spreading velocity was adopted to evaluate the flowability of the eco-concrete. The effective stress was applied to evaluate the buildability of the 3D printing concrete. The interlocking effect of the aggregates on the interfacial bonding between layers was visually validated.